Fishing boat operation mode identification method, device and system - WANG LEI; WANG YINJIE; ZHU YUNYA; GAO BINGTAO; ZHANG LI; ZHAI ZHENGANG (2020)
The invention discloses a fishing boat operation mode identification method, a fishing boat operation mode identification device and a fishing boat operation mode identification system. The fishing boat operation mode identification method comprises the following steps of: performing fusion arrangement on collected multi-source heterogeneous data to obtain fused data; constructing a feature spacebased on the fusion data, and extracting a feature vector corresponding to each fishing boat in the fusion data according to the feature space to obtain a plurality of feature vectors; training a classification model by utilizing the plurality of feature vectors to obtain a classification model capable of identifying each fishing boat operation mode; and when the fishing boat operation mode is identified, inputting the acquired operation data of the fishing boat into the classification model, and identifying the operation mode of the fishing boat by using the classification model. 本发明公开一种渔船作业方式识别方法、装置与系统。本发明的方法包括：对收集到